Clinical Profile of Carcinoma Rectum and Treatment Modalities with Outcome– An Observational Study - Dr.R.Ganesan3 , Dr.D.Latha1 , Dr.P.Jaya, Dr.S.Thirumalai Kannan1 , * Dr.K.S. Goku Dr.D.Maruthupandian1 , Dr.K.Karunakaran (International Journal of Scientific Research and Management (IJSRM), 2017)
Aim : To determine the incidence of age, sex, clinical manifestations, site, stages of carcinoma rectum and morbidities, mortality following surgery. To evaluate surgical modalities and neoadjuvant chemoradiation in carcinoma rectum. Materials and Methods: This study has been conducted in the Department of Surgery, Govt. Rajaji Hospital, Madurai during 2009- 2011. All patients underwent clinical examination and appropriate investigations to confirm and stage the disease. Patients who were included in neo adjuvant therapy, chemo radiation and surgery were followed. Postoperative adjuvant chemotherapy was also given. Patients were followed up for 1 year. Results: Out of 50, majority of carcinoma rectum cases occurs in 5th decade (28%) with male:female ratio 2:1. The predominant symptoms were bleeding per rectum(76%),constipation(58%) and pain(24%). Commonest site was lower 1/3rd of rectum(54%). Majority of the patients were in stage III( 48%),stage I and II(36%)and stageIV(8%). 20 patients underwent abdomino perineal resection(44%), 10 patients underwent laproscopic assisted abdomino perineal resection(22%), 7 patients underwent anterior resection(16%),8 patients underwent emergency colostomy and 5 patients were inoperable for whom palliative chemotherapy / radiotherapy was given. Neo adjuvant chemoradiation was given in 5 patients with stage III. Out of which anterior resection was done in 3 patients(60%) and APR was done in 2 (40%). The most common post operative morbidity was perineal wound infection(16.6%),Perineal wound gaping( 3.3%), Abdominal wound infection( 2.2%). Retention of urine in 2 patients and impotence in 1 patient. Less postoperative complications were noted with inceasing age of the patients(P